Pendampingan Sosial Melalui Edukasi Bahaya Gadget pada Anak di Bangka Jaya Kecamatan Dewantara Kabupaten Aceh Utara - Rahman, Dahlan A.; Zulhilmi; Bin Abubakar, Muhammad; Faisal, Naidi; Abdullah, Taufik; M. Rizwan (Universitas Malikussaleh, 2025)
Gadgets are digitally multifunctional communication tools in helping us provide information that is global in nature. So gadgets themselves have also become a trend in the world of children because of the various game facilities offered. Gadgets also make children get carried away by the impact and influence on their behavior so that many problems occur in the aspect of bad behavior. Children's souls are playing, of course, with the presence of gadgets, it has a huge impact on their growth and development. The majority of people spend a lot of time using gadgets every day. This is what happened to children in Bangka Jaya Village where the influence of gedget was very large. This is also inseparable from the role of parents towards their children. The implementation of community service in Bangka Jaya village, Dewantara district, North Aceh Regency is related to these problems. Therefore, the implementation of this PkM activity is expected to be able to improve the character of children who are virtuous and have good intelligence and mentality. This needs to be built in providing room for actualization for children but under parental control, including in the use of gadgets. In addition, the role of teachers and also the community is needed to support externally or positive support from outside the home. So Bangka Jaya village, Dewantara district, North Aceh Regency is expected to be able to implement this PkM application in the midst of its community.